Carotid stiffness is associated with retinal microvascular dysfunction—The Maastricht study. (6th May 2021) - van der Heide, Frank C. T.; Zhou, Tan Lai; Henry, Ronald M. A.; Houben, Alfons J. H. M.; Kroon, Abraham A.; Dagnelie, Pieter C.; van Dongen, Martien C. J. M.; Eussen, Simone J. P. M.; Berendschot, Tos T. J. M.; Schouten, Jan S. A. G.; Webers, Carroll A. B.; Schram, Miranda T.; et al.
Abstract: Objective: This study investigated whether arterial stiffening is a determinant of subtle retinal microvascular changes that precede diabetic retinopathy. Research design and methods: This study used cross‐sectional data from the Maastricht Study, a type 2 diabetes‐enriched population‐based cohort study. We used multivariable linear regression analysis to investigate, in individuals without and with type 2 diabetes, the associations of carotid distensibility coefficient and carotid‐femoral pulse wave velocity with retinal microvascular diameters and flicker light‐induced dilation and adjusted for cardiovascular and lifestyle risk factors. Results: The retinal microvascular diameter study population consisted of N  = 2434 participants (51.4% men, mean ± SD age 59.8 ± 8.1 years, and 28.1% type 2 diabetes). No measures of arterial stiffness were significantly associated with microvascular diameters. Greater carotid distensibility coefficient (i.e., lower carotid stiffness) was significantly associated with greater retinal arteriolar flicker light‐induced dilation (per standard deviation, standardized beta [95% CI] 0.06 [0.00; 0.12]) and non‐significantly, but directionally similarly, associated with greater retinal venular flicker light‐induced dilation (0.04 [−0.02; 0.10]). Carotid‐femoral pulse wave velocity (i.e., aortic stiffness) was not associated with retinal microvascular flicker light‐induced dilation. The associations between carotid distensibility coefficient and retinal arteriolar and venular flicker light‐induced dilation were two‐ to threefold stronger in individuals with type 2 diabetes than in those without. Conclusion: In this population‐based study greater carotid, but not aortic, stiffness was associated with worse retinal flicker light‐induced dilation and this association was stronger in individuals with type 2 diabetes. Hence, carotid stiffness may be a determinant of retinal microvascular dysfunction.